Sprint vs. interval training in football - Bravo, D. F.; Impellizzeri, F. M.; Rampinini, E.; Castagna, C.; Bishop, D.; Wisloff, U. (International Journal of Sports Medicine, 2008)
The aim of this study was to compare the effects of high-intensity aerobic interval and repeated-sprint ability (RSA) training on aerobic and anaerobic physiological variables in male football players. Forty-two participants were randomly assigned to either the interval training group (ITG, 4 × 4 min running at 90 - 95 % of HRmax; n = 21) or repeated-sprint training group (RSG, 3 × 6 maximal shuttle sprints of 40 m; n = 21). The following outcomes were measured at baseline and after 7 weeks of training: maximum oxygen uptake, respiratory compensation point, football-specific endurance (Yo-Yo Intermittent Recovery Test, YYIRT), 10-m sprint time, jump height and power, and RSA. Significant group × time interaction was found for YYIRT (p = 0.003) with RSG showing greater improvement (from 1917 ± 439 to 2455 ± 488 m) than ITG (from 1846 ± 329 to 2077 ± 300 m). Similarly, a significant interaction was found in RSA mean time (p = 0.006) with only the RSG group showing an improvement after training (from 7.53 ± 0.21 to 7.37 ± 0.17 s). No other group × time interactions were found. Significant pre-post changes were found for absolute and relative maximum oxygen uptake and respiratory compensation point (p < 0.05). These findings suggest that the RSA training protocol used in this study can be an effective training strategy for inducing aerobic and football-specific training adaptations.